Nanomaterials for Postharvest Management of Insect Pests: Current State and Future Perspectives - Jasrotia, Poonam; Nagpal, Mohini; Mishra, Chandra Nath; Sharma, Amit Kumar; Kumar, Satish; Kamble, Umesh; Bhardwaj, Ajay Kumar; Kashyap, Prem Lal; Kumar, Sudheer; Singh, Gyanendra Pratap (Frontiers in Nanotechnology, 2022)
Globally, between one quarter and one-third of total grains produced each year are lost during storage mainly through infestation of insect pests. Amongst the available control measures such as chemical, physical techniques, etc., fumigation with aluminum phosphide (AlP) is so far considered as the best control option against storage insect pests. However, these insect pests are now developing resistance AIP due to its indiscriminate use under the absence of any alternative control option. Not only resistance to AIP is rising, but also its inhalation has shown adverse effects on animals and human beings. In an era of modern science, nanotechnology has opened up a wide range of opportunities in various fields like agriculture (pesticides, fertilizers, etc.), pharmaceuticals, and electronics. One of the applications of nanotechnology is the usage of nanomaterials-based insecticides formulations for mitigating field and storage insect pests. Several formulations viz., nanoemulsions, nanosuspensions, controlled release formulations, solid-based nanopesticides have been developed with different mode of action and application. The major advantage is their small size which helps in proper spreading on the pest surface and thus, better action than conventional pesticides is achieved. Besides, their minute size, these have no or reduced harmful effects on non-target species. Nanopesticides can therefore provide green and efficient alternatives for the management of insect pests of field and storage. However, an outcry against the utilization of nano-based pesticides is also revealed. It is considered by some that nano-insecticides may also have hazardous effects on humans as well as on the environment. Due to limited available data, nanopesticides have become a double-edged weapon. Therefore, nanomaterials need to be evaluated extensively for their large scale adoption. In this article, we reviewed the nanoformulations that are developed and have proved effective against the insect pests under post-harvest storage of grains.